IMPLEMENTASI METODE FUZZY SERVQUAL DAN QUALITY FUNCTION DEPLOYPMENT TERHADAP KUALITAS LAYANAN BPJS KESEHATAN RSUP H. ADAM MALIK - Indah Simamora; Ratna Wahyuni (Universitas Quality, 2019)
Along with the increase in the number of human population and economic conditions that are increasingly advanced, the public awareness of health is increasing. In addition, currently access to services for the Social Security Administering Agency (BPJS) is getting wider, the hospital must be able to add capacity to existing facilities and improve the quality of services. This study aims to implement the Fuzzy Servqual method and Quality Function Deployment on the quality of BPJS Health services in H. Adam Malik Hospital and determine which attributes are priority improvements. Data processing based on the criteria of the Fuzzy-Servqual method by determining fuzzy sets, fuzzyfication and defuzzyfication. determine the Gap and determine the priority of improvement using the Quality Function Deployment method. The results of this study indicate that all 19 BPJS service attributes provided by applying the Fuzzy Servqual method still do not meet patient expectations, because the value of patient satisfaction with services is still lower than the expectation value. Attributes that must be prioritized to improve their quality, namely: Revelation Attribute of Q2 with a gap value -3.68, Revelation Attribute of Q7 with a gap value of -1.58., Revelation Attribute of Q12 with a gap value of -1.58. The technical response that became the main target was the Procurement of Excellent Training Services, the addition of AC Fan in the inpatient room, making improvements to the facilities and infrastructure.